Assessment of Knowledge, Attitude and Practice based Survey on the Use of Ultrasonics in Endodontics among Practitioners (Indian Journal of Forensic Medicine & Toxicology, 2020)
During the past few centuries, endodontics has benefitted from the latest technologies and new techniques,Ultrasonics being one of them. Ultrasonics in endodontics has been used for various purposes such asrefining of access cavities, irrigation, removal of pulp stones/ metallic posts/ fractured instruments. It is alsobeing used in surgical endodontics which include procedures such as root end resection and microsurgeries.Ultrasonics thus plays a key role in the successful outcome of endodontic therapy. The present survey wasconducted among postgraduate students in endodontics, general dental practitioners and endodontists. Theaim of the present survey is to assess the knowledge, attitude and practice regarding the use of ultrasonicsin endodontics among practitioners. Questionnaire based survey comprising 19 questions divided intoknowledge based, attitude based and practice based questions. The questionnaire was circulated via electronicmedia through mails. A 200 responses were received from the respondents,.The responses were viewed inM.S. office excel and the results were interpreted using graphs by SPSS 23.0 Version.39% of postgraduates inendodontics, 40% of Endodontist and 21% of general dentists participated in this survey.This survey enablesthe reader to get a better understanding of the precise and indispensable use of ultrasonics in endodonticpractice. Within the limitations of the study, it shows that the knowledge with respect to ultrasonics inendodontics is moderate compared to attitude and practice among respondents.This survey indicated theneed for educational intervention to improve the knowledge,attitude and practice on the use of ultrasonicsin endodontics among dentists.
Keywords: Applications of Ultrasonics; Endodontics; Endosonics; KAP survey; Ultrasonics.